First record of Halictoxenos Pierce (Strepsiptera: Stylopidae) from Mexico with the description of a new species parasite of Lasioglossum exiguum (Smith) (Hymenoptera: Halictidae) - Quintos-Andrade, Gerardo; Valenzuela-González, Jorge E. (Zootaxa, 2024)
Halictoxenos is a genus of parasites with a mainly holarctic distribution and exclusive parasite of bees of the Halictinae subfamily. In this work, we describe a new species from Mexico, parasite of the halictid Lasioglossum exiguum and with a known distribution in locations of central and southern Veracruz. The delimitation of this species is supported by morphological and molecular evidence. A diagnosis for Halictoxenos and certain characters for species delimitation is also proposed. It is expected that this research may be a steppingstone to the continuity of the study of Halictoxenos and the Stylopidae family in Mexico and the American continent.